2019
DOI: 10.7861/clinmedicine.19-2-s140
|View full text |Cite
|
Sign up to set email alerts
|

A renal genetics clinic – model for our times

Abstract: A renal genetics clinic -model for our times AimsSignificant advances in the technology, cost and speed of processing, and interpretation of complex genetic information are offering new opportunities to incorporate genetics and genomics into routine healthcare; here we evaluated our multidisciplinary renal genetics clinic to provide insights into how similar services, incorporating genetics expertise embedded within other medical specialties, might be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…If patients require genetic testing but there are barriers to being seen in a Medical Genetics clinic, primary care providers and other specialists may order genetic testing on their own without genetics support (Shields, Burke, & Levy, 2008), even though literature has shown that these providers have little experience or training in genetic testing (Greendale & Pyeritz, 2001; Mainous, Johnson, Chirina, & Baker, 2013). Other institutions have set up joint kidney genetics clinics, staffed by nephrologists, genetic counselors, and geneticists, which see 30–160 patients per year (Adalat, Bockenhauer, Ledermann, Hennekam, & Woolf, 2010; Alkanderi, Yates, Johnson, & Sayer, 2017; Mallett, Corney, McCarthy, Alexander, & Healy, 2015; Mallett, Fowles, McGaughran, Healy, & Patel, 2016; Robinson, Sandford, Wiseman, Sarker, & Karet Frankl, 2019; Thomas et al, 2020). These workforce shortages lead to delayed appointments, and thus, delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…If patients require genetic testing but there are barriers to being seen in a Medical Genetics clinic, primary care providers and other specialists may order genetic testing on their own without genetics support (Shields, Burke, & Levy, 2008), even though literature has shown that these providers have little experience or training in genetic testing (Greendale & Pyeritz, 2001; Mainous, Johnson, Chirina, & Baker, 2013). Other institutions have set up joint kidney genetics clinics, staffed by nephrologists, genetic counselors, and geneticists, which see 30–160 patients per year (Adalat, Bockenhauer, Ledermann, Hennekam, & Woolf, 2010; Alkanderi, Yates, Johnson, & Sayer, 2017; Mallett, Corney, McCarthy, Alexander, & Healy, 2015; Mallett, Fowles, McGaughran, Healy, & Patel, 2016; Robinson, Sandford, Wiseman, Sarker, & Karet Frankl, 2019; Thomas et al, 2020). These workforce shortages lead to delayed appointments, and thus, delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%